Potensi Sektor Pertanian Dalam Pembangunan Wilayah Kabupaten Pasaman - Syahrial; Dermawan, Alvindo; Aulia Putri, Syilvia (JURNAL ILMIAH AGRINECA, 2024)
Regional development aims to increase regional economic growth, reduce regional disparities and increase regional competitiveness. The agricultural sector is a sector that has an important role in the regional economy. In an effort to accelerate regional development growth, further analysis of the development of the agricultural sector is needed. The objectives of this research are 1) to analyze the development of the agricultural sector in Pasaman Regency, 2) to analyze the pattern and structure of the agricultural sector in Pasaman Regency. The analysis method used is the Entropy Diversity Index (IDE) and Klassen Typology. The results of the analysis are that the agricultural sector in Pasaman Regency is not developing because it has an IDE value < 1, rice, corn, banana and rambutan are included in the leading commodities (quadrant I), durian and palm oil are included in the potential sector (quadrant II), salak, rubber , cocoa, areca nut and coconut are included as commodities. developing (quadrant III), cassava, sweet potatoes, peanuts and oranges are among the underdeveloped sectors (quadrant IV).